Spreadsheet Error Detection and Debugging Approach for Dynamic Discrete Inventory Control Models - Djordjevic, Lena; Lecic-Cvetkovic, Danica; Makajic-Nikolic, Dragana; Babarogic, Sladjan; Omerbegovic-Bijelovic, Jasmina (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Spreadsheets have been widely used in many business and scientific areas for modeling and simulation. Nevertheless, a number of research surveys have shown that these applications are particularly prone to errors. Some of the reasons for this error-proneness can be attributed to the fact that spreadsheet models are usually developed by the end-users and that standard software quality assurance processes are typically not applied. In addition, end-users often don’t have a "clear picture" about the model structure and elements represented in the spreadsheet. The paper presents error detection and debugging approach developed for dynamic discrete spreadsheet models of inventory control. Spreadsheet modeling of inventory dynamics is based on the utilization of the discrete-time system control concept. This concept provides additional rules (common and specific constraints) which can be used for error detection. Preliminary experiments show general applicability of the approach.